The Practices of Clientelism and Vote Buying in Social Policy: Case Study of Bintan Prosperous Cards - Yudiatmaja, Wayu Eko; Samnuzulsari, Tri (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2018)
This study looks into clientelism and vote buying on Bintan Prosperous Cards (Kartu Bintan Sejahtera, KBS) in Bintan, Kepulauan Riau. The objective of this study is to understand the practices of clientelism and vote buying using KBS. This study was conducted by case study approach. The participants of this study consist of the Commission of General Election of Kepulauan Riau, candidates of governor of Kepulauan Riau 2015-2020, candidates of Bintan Regent 2015-2020, their supported parties, successful and campaign team, and the bureaucracy implementing KBS. The findings of this study are that KBS were used as the practices of clientelism and vote buying both by the candidates of Kepulauan Riau governor and the candidates of Bintan Regent, 2015-2020 period. This study also finds that formal and informal political networks are utilized by the candidates as a clientelism and vote buying arenas. This study not only contributes to the literature of clientelism and vote buying, but also adds the literature of social policy in the context of Indonesian local politics setting